Target marketing in the health services industry: the value of journeying off the beaten path - James K. Elrod; John L. Fortenberry (BMC, 2018)
Abstract Background Target marketing, a practice used to more effectively address the wants and needs of customers, involves three interrelated activities: market segmentation, targeting, and product positioning. The practice follows a perfectly logical process. For a given offering, healthcare institutions select a desired group to pursue and arrange service characteristics and related attributes in a manner to entice that particular group to forward patronage and become customers. Pursuits often focus on heavily-traveled routes teeming with competitors, but occasionally an off the beaten path can be identified to amplify target marketing efforts. Discussion In an earlier chapter of its history, Willis-Knighton Health System identified and pursued an off the beaten path in its bid to capture market share in pediatric healthcare services. The direct route-targeting current and prospective parents-was heavily pursued by competitors, prompting the institution to seek a unique approach; a road less traveled which would reach the same audiences but do so via a different route. Children, as direct care recipients, supplied one such route, and while their ability to influence associated parental decisions was unclear, the institution viewed developing a bond with them to have great potential. Painstaking efforts yielded Willis-Knighton Health System's Pediatric Orientation Program, fostering an affinity between the institution and children, which in turn influenced parents, affording opportunities for enhanced patronage in pediatric medicine and beyond. Conclusions Willis-Knighton Health System's decision to look off the beaten path for an avenue capable of amplifying its target marketing initiatives resulted in a novel pursuit which distinguished the institution from its competitors and set the stage for achieving its goal of providing healthcare services for a greater percentage of children in the marketplace. Additional spillover effects bolstering share in other areas also were afforded. This unique initiative addressed desires to pursue an increasingly important road less traveled to reach prime audiences. When roads less traveled can be identified, opportunities abound for better connecting with customer groups, warranting investigation and pursuit.